1987
DOI: 10.21273/jashs.112.5.783
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ in Cell Walls of Ripening Tomato and Peach

Abstract: Ca2+ content in cell wall-middle lamella (CW–ML) areas of outer and inner pericarp, placenta, and gel parenchyma of ripening tomato (Lycopersicon esculentum Mill. cvs. Celebrity and Jumbo) and mesocarp of ripening peach [Prunus persica (L.) Batsch cv. Georgia Belle] was determined by energy dispersive (EDS) X-ray microanalysis. Ca2+ increased from 1.50 to 6.95 mg·g–1 dry weight in CW–ML of outer pericarp and 0.98 to 2.60 mg·g–1 dry weight in CW–ML of inner pericarp during ripening. Ca2+ content remained consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(1 citation statement)
references
References 23 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Regarding utilization of calcium during the post -harvest of fruit, studies were conducted to show that it reversed their qualities, impeded physiological disorders, reduced the rate of respiration and slowed the ripening process in apple, tomatoes and peaches (Burns and Pressey, 1987). It was also observed that the post-harvest life of apples and tomatoes was prolonged, firmness improved and rottenness reduced during the storage under influence of calcium (Nirupama et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding utilization of calcium during the post -harvest of fruit, studies were conducted to show that it reversed their qualities, impeded physiological disorders, reduced the rate of respiration and slowed the ripening process in apple, tomatoes and peaches (Burns and Pressey, 1987). It was also observed that the post-harvest life of apples and tomatoes was prolonged, firmness improved and rottenness reduced during the storage under influence of calcium (Nirupama et al, 2010).…”
Section: Discussionmentioning
confidence: 99%